Effect of fly ash cenosphere pore formers on the microstructure and mechanical properties of vitrified diamond grinding wheels. (September 2017) - Yin, Yuhang; Fang, Jiabin; Xue, Qunhu
Abstract: This paper focuses on the influence of fly ash cenosphere (as a pore former) content and particle size on the porosity, microstructure and mechanical properties of vitrified bond diamond tools. The sintered specimens were examined using comprehensive thermal analysis, X-ray diffraction, Raman spectroscopy, scanning electron microscopy, three point bending tests and porosity measurements. The porous morphological parameters (volume, size and distribution of pores) of the sample correlated with the content and size of the fly ash cenosphere, and diffusion layers were formed between the pore former and the vitrified matrix. The bending strength of the porous vitrified matrix varied between 27.28 and 35.92 MPa as the porosity changed from 40.66–43.97%. Based on response surface methodology (RSM) studies, two second-order response models for the open porosity and bending strength were established, and the utilization of the response surface model was evaluated with regards to the content and size of fly ash cenosphere present. Highlights: Vitrified diamond composites with controlled porosity, pore shape and size were fabricated using fly ash cenosphere. Diffusion mechanism was proposed at the interface of pore former and bond, which contributes to the strength of composites. Based on response surface methodology (RSM) model, the optimal adding scheme of pore former was put forward.